Pengaruh Bauran Pemasaran Terhadap Loyalitas Melalui Kepuasan Pelanggan Dalam Menggunakan Layanan PLN Mobile - Nasrul, Rezki; Syamsul Ridjal; Dharmawaty Djaharuddin; Yana Fajriah; Rezki Arianty Akob (Al-Buhuts, 2025)
This study aims to determine the direct effect of marketing mix variables and the direct effect of customer satisfaction on customer loyalty and the indirect effect of marketing mix variables on customer loyalty with customer satisfaction as an intervening variable at PT PLN (Persero) UP3 Makassar Utara. The population in this study were 172,313 customers. The results of the questionnaire have been tested for validity and reliability using the PLS model scheme and model evaluation, have also been tested for inner model evaluation with the determinant coefficient test, model goodness test and hypothesis testing both directly and indirectly. The results of this data processing use SmartPLS version 4. The results of the study directly show that the marketing mix has a positive and significant effect on customer loyalty, then the customer satisfaction variable has a positive and significant effect on customer loyalty. While the indirect research results show that the marketing mix has a positive and significant effect on customer loyalty, then the customer satisfaction variable has a positive and significant effect on customer loyalty.